THE SCIENCE- THE MOST IMPORTANT RESOURCE OF ECONOMIC AND SOCIAL STATE DEVELOPMENT - Xamdamova Gavxar Absamatovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discussesdevelopment prospects science - as the most important resource for the economic and social development of each state, guaranteeing citizens a decent standard of living, democratic organization of society, high standards of culture. Wherescience, technology and innovation are designed to stimulate the pursuit of more equitable and sustainable development.